Banyan Tree - Mumbai Archive Project Team (Jio Institute, 2024)
Residents of Kandivli village, primarily from the Koli, Pathare Prabhu, and Agri communities, tie threads around the banyan tree (Ficus benghalensis). Hindus consider the banyan tree sacred due to its long lifespan, symbolizing everlasting longevity.